ACCELERATED HYPERFRACTIONATED RADIOTHERAPY IN THE TREATMENT FOR INOPERABLE, LOCALLY ADVANCED GASTRIC CANSER - S. S. Litinskiy; A. A. Ruzhnikova; S. M. Asakhin; A. О. Ruzhnikv; M. Yu. Valkov (Сибирский онкологический журнал)
Purpose: to compare survival of patients with locally advanced inoperable gastric cancer (LAIGC), receiving accelerated hyperfractionated (AHF) or conventionally fractionated (CF) radiation therapy (RT). Methods and Materials. Between November 1993 and March 2010, 137 patients with LAIGC receiving CF (2 Gy daily) or AHF (1.3 Gy b.i.d.) to total at least 50 Gy RT in combination or without chemotherapy were retrospectively selected from the hospital database of Arkhangelsk clinical oncological dispensary. Overall survival (OS) assessed using actuarial analysis, Kaplan – Meier method and Cox regression. results. The CF and AHF groups were 102 and 35 patients, respectively. Median follow-up time for all patients was 12 years. By the time of analysis 123 (90 %) patients of all cohort died. Median, 7-year survival were 24 (95 % confidence intervals (CI), 17–31) vs 16 (95 % CI, 11–21) months, hazard ratio (HR)=0.71 (95 % CI, 0.46–1.06), р=0.097; and 19 % (95 % CI 8–34 %) vs 6% (95 % CI 2–13 %) in the AHF and CF groups, respectively. In multivariate OS model the difference decreased to HR=0.87 (95 % CI, 0.49–1.55). The location of the tumor in median third (HR=0.60, 95 % CI, 0.37–0.99 in refer to upper third) was the only independent factor influencing survival.  There was no influence of the total dose in chosen level on survival. conclusion. Our retrospective shows trend towards better OS for those LAIGC patients receiving RT in AHF regimen compared to CF. The prospective randomized study with conformal radiation technics is necessary to confirm these findings.